2017
DOI: 10.1007/s00701-017-3137-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative orofacial pain, temporomandibular dysfunction and trigeminal sensitivity after recent pterional craniotomy: preliminary study

Abstract: There was a high frequency of temporomandibular dysfunction, postoperative orofacial pain and trigeminal sensory abnormalities. These findings can help to understand several abnormalities that can contribute to postoperative headache or orofacial pain complaints after pterional surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…This condition can also initiate inflammatory reactions in the joint, eliciting secondary biomechanical changes and joint pain. Simultaneously, patients with TMDs can have abnormal trigeminal pain processes [ 31 ], which may be related to an imbalance of 5-hydroxytryptamine and catecholamine neurotransmitters. Therefore, psychological or emotional problems are also involved in the pathogenesis of TMDs, emphasizing the significance of mental state evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This condition can also initiate inflammatory reactions in the joint, eliciting secondary biomechanical changes and joint pain. Simultaneously, patients with TMDs can have abnormal trigeminal pain processes [ 31 ], which may be related to an imbalance of 5-hydroxytryptamine and catecholamine neurotransmitters. Therefore, psychological or emotional problems are also involved in the pathogenesis of TMDs, emphasizing the significance of mental state evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Postoperative temporomandibular dysfunction may also play a crucial role in headache formation after pterional craniotomy. 23 In our study, mean AHAC intensity perceived by craniotomy patients with versus without surgically induced muscle damage differed by 1.1 NRS with higher scores following CMI. Headache severity has been clearly shown to be the major determinant of headache-related disability in a large population of migraine patients.…”
Section: Discussionmentioning
confidence: 49%
“…29 Another potentially disabling factor that has recently been identified in a preliminary study is the manifestation of temporomandibular disorders with masticatory dysfunction after pterional craniotomy. 23 An interdisciplinary multimodal approach to the individual patient's needs is necessary to mitigate the burden of acute postsurgery headache as well as its possible detrimental long-term effects. Besides the well-established utilization of opioids, paracetamol/acetaminophen and nonsteroidal anti-inflammatory drugs (NSAIDs) in the acute stage, 9 sufficient AHAC management commonly requires further concerted pre-, intra-, and postoperative measures.…”
Section: Discussionmentioning
confidence: 99%
“…The greater the amount of air in the root of the trigeminal nerve, the more severe the harassment of the trigeminal nerve, and therefore the more severe the postoperative pain. Studies have shown that mechanical or chemical stimulation of the trigeminal nerve is one of the key factors of pain after craniotomy(Zhao and Levy 2014, Brazoloto, de Siqueira et al 2017). However, no research has been found to investigate whether the gas at the root of the trigeminal nerve can cause headaches.…”
Section: Discussionmentioning
confidence: 99%